UNSTEADY PRESSURE DROP AND HEAT TRANSFER OFMAGNETOHYDRODYNAMIC ANNULAR TWO-PHASE INRECTANGULAR CHANNEL - Faisal, Dhefaf; Abdulhadi, Ahmed (Iraqi Journal of Science, 2024)
An annular two-phase, steady and unsteady, flow model in which a conductingfluid flow under the action of magnetic field is concavely. Two models arepresented, in the model one; the magnetic field is perpendicular to the long side ofthe channel, while in the model two is perpendicular to the short side. Also, westudy, to some extent the single-phase liquid flow.It is found that the motion and heat transfer equations are controlled by differentdimensionless parameters namely, Reynolds, Hartmann, Prandtl, and Poiseuilleparameters. The Laplace transform technique is used to solve each of the motion andheat transfer equations. The effects of each of dimensionless parameters upon thevelocity and heat transfer is analyzed.A comprehensive study for Model 1, and 2 is given. Also, a comparison studyamong steady, unsteady, single-phase, two-phase for Model 1, and Model 2 isconsidered.